Entre o ócio e o negócio: possibilidades de desenvolvimento da motricidade escolar - Lemos, Fábio Ricardo Mizuno (Universidade Federal de São Carlos, 2013)
The productive logic invades all aspects of life, including education, and with its ideology power distorts reality and enslaves minds in order to acquire economic advantages. This cunning scheme is developed with the school aid that uses the curriculum components, such as physical education, to perpetuate the mercantile greed, by designing a practice focused on obedient fitness bodies, able to fit into a real paradigmatic business. In opposition to this ideology of quantify the results of the educative business (denial of idle state), it was proposed the development of a action-idleness (idle and fun action, lazy and playful, of a human situated in both actions and values genuinely humans) in the Scholar Physical Education (in three Basic Education schools) of two northern (interior) towns of São Paulo State, in the 2nd half of 2012. To understand the educative processes mobilized by this action, objective of this thesis, we used both Phenomenology and Analysis of the Situated Phenomenon as referential and proceedings methodological, because they allow the interpretation of lived experiences, under the person s inner perspective involved in the research process. With how the unveiled experience from the discourses analysis of both students and participants of the project in the Basic Education schools the human relations valuing and the effective participation in the proposed activities were perceived. In the undergraduates discourses, the first assessment was of doubt about the possibility to effective the action in school, however, the teaching praxis insertion had the perception that they were effectively learning it, because they could live positive experiences in relation to go-beyond the established (paradigm of Human Motricity) for the Scholar Physical Education. Within the major considerations stemming with the research, one may highlight: The necessary of being attentive for the educational pessimism both institutionalized and naturalized; the action must not start with a simulated teaching so that the praxis do not be inauthentic; By Being-More, In-Action, it is possible to change from a productive ethics to an ethics where the greatest goods are the feelings and human relationships.
Keywords: Práticas sociais e processos educativos; Educação Física Escolar; Motricidade Humana; Ócio; Ação Libertadora; Educative Processes; Scholar Physical Education; Human Motricity; Idleness; Liberating Action; CIENCIAS HUMANAS::EDUCACAO